Risk Factors for Development of New-Onset Diabetes Mellitus After Kidney Transplantation - Tariq Shah; Arjang Kasravi; Edmund Huang; Rick Hayashi; Brian Young; Yong W. Cho; Suphamai Bunnapradist (2006)
New-onset diabetes mellitus after kidney transplantation (NODM) is an important co morbid condition that is associated with inferior graft and patient survival. The objective of this study was to identify donor, recipient and transplant factors, and choices of immunosuppression associated with development of NODM using Organ Procurement Transplant Network/United Network of Organ Sharing database (OPTN/UNOS).From January 2004 to December 2005, 15,309 adult kidney transplants alone with at least one follow-up report as of March 2006 were identified in the OPTN/UNOS database. Among these, 1,581 patients developed NODM during the follow-up period. We examined the risk factors of NODM using multivariate Cox regression analysis using the time to diagnosis of NODM as a time-varying end point. Other events such as graft loss, patient death, and lost to follow-up were censored.NODM was reported in 10% in our study population with mean follow-up time of 306 days. After adjusting for other known factors, independent factors associated with the development of NODM included recipient age (29% increase of relative risk [RR] for every 10-year age increment), obesity (RR = 1.39 for body mass index [BMI] 25-30 and RR = 1.85 for BMI > 30 vs. BMI < 25), tacrolimus use (RR = 1.50), hepatitis C virus (HCV) positivity (RR = 1.42), and African-American recipients (RR = 1.32). Alemtuzumab was associated with a lower risk of NODM (RR = 0.52).Using OPTN/UNOS database, we identified risk factors for development of NODM. Some of these factors are potentially modifiable, including obesity, HCV infection, and the use of tacrolimus. Clinical trials are needed to assess whether modifying these "modifiable risk factors" will indeed prevent NODM.